INVESTIGASI PEMAHAMAN MAHASISWA TERHADAP MATERI PERSAMAAN LINIER PADA MASA PEMBELAJARAN JARAK JAUH DI PGSD FKIP UNSYIAH - Linda Vitoria (Jurnal Pesona Dasar, 2020)
The implementation of distance learning for mathematics course at PGSD FKIP Unsyiah may have affected student learning. This article aimed at investigating students’ understanding of linear equation during distance learning. 70 first-year students participated in this study. Data was gathered using a test consisted of 2 word problems about linear equations. Data was analyzed based on the 5 aspects of solving linear equation problems which include using variables, forming equations, solving the equations, performing calculations, and giving final answer. Results show that 20% students used variables correctly, 94% formed the equations correctly, 95.7% solved the equations correctly, 90% performed calculations correctly, and 84% gave the right final answers. Only 3 out 5 aspects satisfied the criteria of good understanding. Therefore, it was concluded that students’ understanding of linear equation during distance learning was not satisfactory. This study implies that more intense communication is needed to help students in their learning during the implementation of distance learning.